Catalyzing co-benefits: how cross-regional coordination accelerates pollution and carbon reduction in China’s Yangtze river economic belt - Yu, Zun; Zhao, Zebin; Zang, Shoujuan; Qu, Aiyu (Frontiers in Environmental Science, 2025)
BackgroundChina faces the dual challenge of pollution control and carbon reduction amid rapid urbanization and industrialization, while traditional environmental policies struggle to meet the demands of cross-regional coordinated governance.MethodsUsing the Outline of YREB as a policy context, this study systematically evaluates the co-benefits and mechanisms of cross-regional coordination policies on pollution and carbon reduction. Based on panel data from 259 Chinese prefecture-level cities (2014–2019), we employ a coupling coordination model and a difference-in-differences approach to assess policy effectiveness.ResultsThe findings reveal that: (1) Cross-regional coordination policies significantly enhance pollution-carbon synergy in YREB cities through structural integration effects, with the impact strengthening over time and remaining robust across tests; (2) The policy facilitates long-term pollution-carbon synergy governance through three key pathways—industrial green transition (structural), clean energy system co-construction (technological), and cross-regional low-carbon technology diffusion (knowledge-based)—driving a shift in environmental governance from policy-driven external enforcement to development-driven endogenous demand.ConclusionThis study highlights that cross-regional coordination is not only a tool for spatial economic integration but also a structural driver of sustainable environmental governance, providing a novel policy pathway for China’s dual-carbon goals and contributing to global climate governance.